GPS scintillation and irregularities at the front of an ionization tongue in the nightside polar ionosphere - van der Meeren, Christer; Oksavik, Kjellmar; Lorentzen, Dag Arne; Moen, Jøran Idar; Romano, Vincenzo (Journal of Geophysical Research: Space Physics, 2014)
In this paper we study a tongue of ionization (TOI) on 31 October 2011 which stretched across the polar cap from the Canadian dayside sector to Svalbard in the nightside ionosphere. The TOI front arrived over Svalbard around 1930 UT. We have investigated GPS scintillation and irregularities in relation to this TOI front. This is the first study presenting such detailed multi-instrument data of scintillation and irregularities in relation to a TOI front. Combining data from an all-sky imager, the European Incoherent Scatter Svalbard Radar, the Super Dual Auroral Radar Network Hankasalmi radar, and three GPS scintillation and total electron content (TEC) monitors in Longyearbyen and Ny-Ålesund, we observe bursts of phase scintillation and no amplitude scintillation in relation to the leading gradient of the TOI. Spectrograms of 50Hz phase measurements show highly localized and variable structuring of the TOI leading gradient, with no structuring or scintillation within the TOI or ahead of the TOI.